Validation of Motor Outcome Measures in Myotonic Dystrophy Type 2 - Montagnese, Federica; Rastelli, Emanuele; Khizanishvili, Nina; Massa, Roberto; Stahl, Kristina; Schoser, Benedikt (Frontiers in Neurology, 2020)
Introduction: Myotonic dystrophy type 2 (DM2) lacks disease-specific, validated, motor outcome measures (OMs), and patients' reported outcomes (PROs). This represents a limit for the monitoring of disease progression and treatment response. Our aim was to identify the most appropriate OMs to be translated in clinical practice and clinical trials on DM2. This study has been registered on clinicaltrials.gov NCT03603171 (https://clinicaltrials.gov/ct2/show/NCT03603171). Methods: Sixty-six patients with genetically confirmed DM2 underwent a baseline and a follow-up visit after 1 year. The tested OMs included: hand opening time, pressure pain threshold (PPT), manual muscle testing (MMT), hand held dynamometry (HHD), scale for the assessment and rating of ataxia (SARA), quantitative motor function test (QMFT), gait stairs Gowers chair (GSGC), 30-s sit to stand test, functional index 2 (FI-2) and 6MWT. The PROs included DM1-Active-C, Rasch-built Pompe-specific activity scale (R-Pact), fatigue and daytime sleepiness (FDSS), brief pain inventory short form (BPI-sf), myotonia behavior scale (MBS), and the McGill pain questionnaire. Results: All patients completed the MBS and the results correlated well with the hand-opening time. The PPT showed a low reliability, no correlation with pain questionnaires, and did not differentiate patients with or without myalgia. Both muscle strength assessments, MMT and HHD, showed good construct validity. The QMFT showed an acceptable ceiling effect (14.5%), good convergent and differential validity and performed overall better than GSGC. The SARA score showed high flooring effect and is not useful in DM2. 6MWT proved a valid outcome measure in DM2. The 30-s sit to stand is a feasible test with good convergent validity, showing a flooring effect of 20% as it cannot be used in more severely affected patients. The FI-2 is time-consuming and has a high ceiling effect. At the 1-year visit the only assessments able to detect a worsening of DM2 were HHD, QMFT, and 6MWT, which are the most sensitive to change, and therefore clinically meaningful OMs in DM2. Conclusion: The clinical meaningful motor outcome measures that best depict the multifaceted phenotype of DM2 and its slow progression are MBS, MMT, or HHD (depending on the clinical setting), QMFT, and the 6MWT.